Medical students' opinion toward the application of complementary and alternative medicine in healthcare - Syed Meraj Ahmed; Mohammed A Al-Mansour; Elsadig Y Mohamed; Khalid A Medani; Sawsan M Abdalla; Waqas S Mahmoud (Saudi Journal of Medicine and Medical Sciences, 2017)
Context: An accelerated approach to popularize complementary and alternative medicine (CAM) in healthcare services has led to the need to assess medical students' knowledge of CAM. Furthermore, their attitude toward its efficacy and usage will determine its growing popularity in healthcare. Another key idea is to integrate CAM with conventional medical teaching to make it a part of the mainstream medical curriculum. The objectives were to assess the medical students' perceptions about integrating CAM with conventional medicine and to assess the attitude of prescribing different CAM modalities to patients presenting with a particular disease or health disorder. Settings and Design: This is a descriptive, institutional based study conducted on undergraduate 3rd year medical students. Materials and Methods: Data were collected by a structured and pretested questionnaire to be filled in by the participants in the presence of the investigator. Statistical data were entered in SPSS software, and descriptive analysis was conducted. Results: Most of the students (74%) agreed that conventional and CAM therapy can be integrated to achieve a better health care outcome. Forty-eight percent of the participants were positive that knowledge of CAM is important since many patients still prefer this option, particularly for chronic illnesses. Conclusions: The students were receptive to the introduction of a new treatment method in their curriculum, which although unconventional, presents an alternative and traditional form of treatment even if it does not have major backing from the scientific community. The participants felt that more knowledge is required to make an informed opinion about its usefulness to the community as a whole.